Nilai Kebudayaan Dalam Tradisi Basale Layang Pada Ritual Pengobatan Suku Anak Dalam - Damanik, Bella Silvesteria; Naula, Neca; Irawan, Candra Rindi; Ananda, Putri; Nurhafifah, Fatia Zulfa; Nurjannah; Sasabila, Alesia; Khoirunnisa, Indah; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the cultural values embedded in the Basale Layang tradition practiced during healing rituals by the Suku Anak Dalam (Indigenous People of the Forest), and to examine its potential transformation into artistic forms as a medium for cultural education. The research adopts a qualitative descriptive approach, utilizing observation, in-depth interviews, and documentation methods. Data were gathered from cultural practitioners, ethnographic records, and written sources related to the Basale Layang practice. The analysis identified three core elements: spiritual, social, and cultural values manifested through healing chants (layang), symbolic objects, and collective community involvement. Findings reveal that Basale Layang holds a profound symbolic structure representing the interconnectedness of humans, ancestors, and the natural cosmos. Ritual chants, sacred objects, and distinctive movement patterns demonstrate potential for transformation into performance arts such as dance and music. This transformation can serve as an educational tool that not only preserves cultural heritage but also enhances character education by introducing values such as solidarity, spirituality, and reverence for ancestral traditions. This study supports the view that traditional arts can function as strategic mediums for cultural revitalization and value-based education within schools. Thus, integrating the values of Basale Layang into arts education contributes significantly to sustaining local identity amidst the forces of globalization.